Controlling crop pest with a farming awareness based integrated approach and optimal control. Issue 6 (14th October 2021) - Abraha, Teklebirhan; Al Basir, Fahad; Obsu, Legesse Lemecha; Torres, Delfim F. M.
Abstract: We investigate a mathematical model in crop pest controlling, considering plant biomass, pest, and the effect of farming awareness. The pest population is divided into two compartments: susceptible pests and infected pests. We assume that the growth rate of self‐aware people is proportional to the density of susceptible pests existing in the crop arena. Impacts of awareness are modeled through the usual mass action term and a saturated term. It is further assumed that self‐aware people will adopt chemical and biological control methods, namely, integrated pest management. Bio‐pesticides are costly and require a long‐term process, expensive to impose. However, if chemical pesticides are introduced in the farming system along with bio‐pesticides, the process will be faster as well as cost‐effective. Also, farming knowledge is equally important. In this article, a mathematical model is derived for controlling crop pests through an awareness‐based integrated approach. In order to reduce the negative effects of pesticides, we apply optimal control theory.